Who buys New Energy Vehicles in China? Assessing social-psychological predictors of purchasing awareness, intention, and policy - Du, Huibin; Liu, Diyi; Sovacool, Benjamin K.; Wang, Yuru; Ma, Shoufeng; Li, Rita Yi Man (Transportation research. Part F, Traffic psychology and behaviour, 2018)
•Subjective norms plays an important role in purchasing intentions.•There is an “awareness-behavior gap” whereby low-carbon awareness has a moderating effect on behavior via psychological factors.•Low-carbon subjective knowledge and low-carbon objective knowledge have different influencing mechanism on purchasing intention.•Acceptability of policies has positive impact on adoption of New Energy Vehicles. This paper investigates the salience of social-psychological factors in explaining why drivers purchase (or fail to purchase) New Energy Vehicles (NEVs)—including hybrid electric vehicles, battery electric vehicles, and fuel cell electric vehicles—in China. A questionnaire measuring six dimensions (including attitudes, subjective norms, perceived behavioral control, personal norms, low-carbon awareness and policy) was distributed in Tianjin, where aggressive policy incentives for NEVs exist yet adoption rates remain low. Correlation analysis and hierarchical multiple regression analyses are applied data collected through 811 valid questionnaires. We present three main findings. First, there is an “awareness-behavior gap” whereby low-carbon awareness has a slight moderating effect on purchasing behavior via psychological factors. Second, subjective norms has a stronger influence on intention to purchase New Energy Vehicles than other social-psychological factors. Third, acceptability of government policies has positive significant impact on adoption of New Energy Vehicles, which can provide reference potential template for other countries whose market for New Energy Vehicles is also in an early stage.